App-supported versus conventional college physical education: Effects on standardized physical fitness scores and exercise motivation in Chinese university students - Xilin Liang; Zenan Wang (PLoS ONE, 2026)
This study evaluated the effectiveness of an app-supported training model versus conventional physical education (PE) on college students’ basic athletic abilities and described exercise motivation in the app-supported condition. A quasi-experimental study was conducted with 90 freshman students over a 10-week period. Participants were assigned to a Treatment Group (n = 45), using the “Campus Sports World” app for guided extracurricular training, and a Control Group (n = 45) following traditional instruction. Physical fitness was assessed pre- and post-intervention using standardized tests for speed, endurance, explosive power, and flexibility. Motivation was assessed post-intervention in the Treatment Group via a questionnaire based on Self-Determination Theory. Results indicated that the Treatment Group achieved significantly greater improvements in speed, explosive power, and flexibility compared to the Control Group. However, no significant difference was found in endurance performance. Furthermore, students in the Treatment Group reported high levels of both intrinsic and extrinsic motivation. These findings suggest that integrating mobile applications into college PE can enhance skill-related fitness, and the observed motivation profile provides context for students’ engagement with the app-supported model, supporting the adoption of blended learning approaches in higher education.